2011
DOI: 10.1007/s11557-010-0734-x
|View full text |Cite
|
Sign up to set email alerts
|

Tomentella alpina and other tomentelloid taxa fruiting in a glacier valley

Abstract: Tomentella is a genus of resupinate basidiomycetes usually fruiting on rotten wood. Ecological studies based on molecular methods have reported many Tomentella species as mycobionts of alpine ectomycorrhizal plants, thus highlighting their importance for plant establishment and development under extreme conditions. For the first time, we report fruiting of eight tomentelloid species in an alpine site, and describe Tomentella alpina as a new species. In the rDNA ITS phylogeny, Tomentella alpina forms a distinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
0
10
0
1
Order By: Relevance
“…The 70-year-old stands were composed of a distinct ectomycorrhizal community, with tomentelloid (Tomentella and Pseudotomentella), Russula, and Inocybe species driving community composition. Although we found that tomentelloid and Inocybe species were abundant in our mature stands, they have been reported across a range of ecosystem development stages, including primary successional habitats (48,49), recently cut/young stands (50)(51)(52), and mature stands (41,53). Species in the Russula genus are more frequently encountered in mature forests (54), but have also been found fruiting in young clear-cuts (55).…”
Section: Discussionmentioning
confidence: 55%
“…The 70-year-old stands were composed of a distinct ectomycorrhizal community, with tomentelloid (Tomentella and Pseudotomentella), Russula, and Inocybe species driving community composition. Although we found that tomentelloid and Inocybe species were abundant in our mature stands, they have been reported across a range of ecosystem development stages, including primary successional habitats (48,49), recently cut/young stands (50)(51)(52), and mature stands (41,53). Species in the Russula genus are more frequently encountered in mature forests (54), but have also been found fruiting in young clear-cuts (55).…”
Section: Discussionmentioning
confidence: 55%
“…Similarly, various taxa previously reported from fruiting body surveys in the Bavarian Alps and adjacent regions were also identified by our Illumina MiSeq sequencing (see S2 Table). Among the most common taxa (see Table 1) were Tomentella alpina recently described by Peintner and Dämmrich [68] from the Tyrolean Alps and Cortinarius subtortus that is a typical ECM species growing between Sphagnum in the Bavarian Alps. On the other hand, several of the abundant taxa are characterized by conspicuous fruiting bodies, which, based on our basidiomata/ascomata surveys and literature do not occur in the study area.…”
Section: Discussionmentioning
confidence: 99%
“…However, T. albomarginata differs from T. sublilacina by having the dark brown to umber hymenophore and monomitic rhizomorphs (Kõljalg 1996;Larsen 1970), and we suggest that T. albomarginata and T. sublilacina should be kept as two independent species. T. bresadolae was reported to be a synonym of T. stuposa (Kõljalg 1996;Daemmrich 2006;Peintner and Dä mmrich 2012), but the previous study has shown that they may represent the different species (Kuhar et al 2016), and our molecular phylogenetic analyses showed T. bresadolae were distantly from T. stuposa again. Here we suggested to keep them as different species.…”
Section: Resultsmentioning
confidence: 51%